STAKEHOLDER COLLABORATION IN ENHANCING THE QUALITY OF PUBLIC SERVICES THROUGH COMMUNITY POLICING: A CASE STUDY OF THE PURWAKARTA DISTRICT POLICE (Lex localis - Journal of Local Self-Government, 2025)
This study aims to evaluate the implementation of Community Policing (Polmas) as a strategy to improve the quality of public services in the areas of public safety and order, using a case study of the Purwakarta District Police. The research is motivated by the rising crime rates in Indonesia, which call for a policing approach based on partnerships between law enforcement agencies and the community. Through the establishment of the Police–Community Partnership Forum (Forum Kemitraan Polisi dan Masyarakat/FKPM), the Purwakarta District Police seeks to adopt a collaborative governance model that emphasizes active stakeholder participation. This study employs a qualitative approach using the collaborative governance framework developed by Ansell and Gash as the analytical lens. The findings reveal that the success of community policing implementation is significantly influenced by the initial conditions of collaboration, facilitative leadership, institutional design, and collaborative processes involving face-to-face dialogue and the development of shared understanding. Nonetheless, several challenges—such as limited personnel competencies, low levels of public trust, and inadequate policy and infrastructure support—serve as critical barriers. This research contributes to the development of collaborative governance theory in public service delivery and offers strategic recommendations to strengthen community policing as a sustainable model of participatory law enforcement.